A measurement of crime control-based social exclusion - García-España, Elisa (My University, 2016)
Comparative criminal justice policy has a strong inclination to confront national crime control systems in accordance to corresponding levels of punitiveness. Some author (Díez-Ripollés, 2011, 2013) has advocated for a more enriched and comprehensive comparative framework, which is founded in either the social inclusion or the social exclusion effects that different crime control systems entail on three specific groups: suspects, offenders and ex-offenders. To this end, it identifies nine topic pools (control of public spaces, legal safeguards, sentencing and sanctions systems, harshest penalties, prison rules, preventive intervention, legal and social status of offenders and ex-offenders, police and criminal records, youth criminal justice), each of them comprising a number of punitive rules or practices. Assuming this model, we are designing and validating a comparative instrument able to measure current criminal policy of Western industrialized countries in accordance to the social inclusion / social exclusion dimension. In order to achieve this goal we have chosen a methodology, which intends to establish an inter-judge agreement on the social exclusive character of a certain amount of punitive rules and practices previously included within those pools. In this presentation, we will explain how we designed the questionnaire sent to the experts, as well as the results of the first validation process. This took place with the cooperation of over 70 international experts from 18 different Western industrialized countries. The inter-judge agreement on the punitive rules and practices capable of producing significant social exclusive effects on the three studied groups was verified through inter-rater reliability (IRR) statistical tests, like the Intraclass Correlation Coefficient (ICC) and Aiken's V Coefficient. We will also describe the pending validation process. Once available, we intend to draw attention of the criminological community to this tool for comparing national crime control systems, and to promote its application.
Keywords: Derecho penal; Exclusión social; Social exclusion; Criminal justice policy